PHILOSOPHICAL SUFISM AS THE CONCEPTUAL FOUNDATION OF ISLAMIC LEADERSHIP ETHICS - Faqihudin, Muhamad; Jinan, Mutohharun (Program Studi Ilmu Tasawuf Universitas Pangeran Diponegoro Nganjuk, Jawa Timur, 2026)
The phenomenon of narrowing the meaning of leadership in modern organizations that are oriented towards technocratic achievements and performance indicators has led to moral degradation and the normalization of ethical deviations. In this context, Islamic leadership demands an ethical foundation that is not only normative, but also touches the inner consciousness of leaders. This article aims to formulate philosophical Sufism as the conceptual basis of Islamic leadership ethics through an examination of the ontological, epistemological, and ethical dimensions in the Sufi tradition. The research uses a qualitative method with a literature review approach, examining classical and modern works by figures such as Ibn 'Arabi and Suhrawardi, as well as contemporary literature on Islamic ethics and leadership. The results of the study show that philosophical Sufism, through the concepts of wahdat al-wujud, fana', and baqa', forms a framework of consciousness that places authority as a trust, not an expansion of the ego. Fana' marks the process of ego decay and the drive for power, while baqa' reinforces the moral steadfastness and moral stability of leaders. Therefore, philosophical Sufism provides an ontological and epistemological foundation for the formation of a more solid ethical disposition than normative and compliance approaches. In conclusion, Islamic leadership ethics should be understood as an architecture of consciousness that shapes actions, not merely rules of behavior. The implications of this study emphasize the need for spiritual guidance and ethical reflection integrated into leadership development so that the values of trustworthiness, justice, and accountability can endure under the pressures of modern organizations